Integrating the Problem-Based Learning Approach Into a Web-Based English Reading Course. (March 2018) - Lin, Lu-Fang
This study incorporated the problem-based learning (PBL) approach into a web-based English reading course. The purpose of the study was to examine the impact of PBL on the participants' English reading comprehension (RC) and to explore the participants' perceptions of PBL. The present study conducted a comparison of two teaching methods. Two classes of university students were randomly assigned to PBL and non-PBL groups. The PBL group was directed by the problem and surveyed the Internet to identify solutions. The non-PBL group was instructed using the teacher-lecture method. The two groups completed RC pre- and posttests, an instructional questionnaire, and self-reports. The statistic results showed that the PBL group achieved significantly higher mean scores than the non-PBL group in English RC. Additionally, the questionnaire results demonstrated that PBL significantly enhanced the participants' active learning and synthesized their cognitive processing. Instructional recommendations for PBL web-based English curricula are presented.